Diseño de un procedimiento de inspección para el sistema neumático de la aeronave A320 mediante el análisis termográfico (2020)
Non-destructive testing has long played an important role in the diagnostic and maintenance processes of civil aviation. Currently, thermographic tests make it possible to identify sources of leaks in aircraft components, as well as to identify insulation losses and electrical failures. In this work, an infrared thermography inspection procedure for the ducts, joints and connections of the elements that make up the air conditioning supply units of the Airbus A320 aircraft is consigned and described in detail, based on the principles of inspection for systems mechanical, electrical and pneumatic as well as the physical principles of infrared radiation. Field tests were carried out to inspect the components that make up the two PACKS units of an aircraft with regional operation in Colombia and, by analyzing the thermograms, it was possible to find pneumatic and water leaks in the joints and bodies of different components. of the aircraft's air conditioning system. For the development of the tests, a medium resolution FLIR thermographic camera was used and factors related to the quality of the images were taken into account, such as focus, distance and emissivity of the materials present in the units. It was found that it is possible to use thermography as a means of inspection of air conditioning pneumatic systems of passenger transport aircraft and gives rise to the design of inspection protocols for more pneumatic systems of commercial aircraft. It was possible to visualize that thermogram affectations may occur due to mechanical discontinuities of aircraft components, as well as improper interpretations of temperature patterns related to the presence of foreign materials on the surface of the components of the PACKS units. However, it is possible to solve these problems with adequate knowledge of the systems to be inspected and the use of infrared thermography for pneumatic units can become a backup process for the visual inspections that are currently the only way to verify the integrity of the components of the air conditioning units of the Airbus A320 aircraft.